Europe 2030 - Benjamin, Daniel, 1961- (Washington, D.C. : Brookings Institution Press, 2010)
"Contributors, with insight and drawing on in-depth knowledge of European affairs over the last forty years, describe the European Union's current strengths and weaknesses and forecast its future development"--Provided by publisher.
Includes bibliographical references and index.
Keywords: European Union -- Forecasting; European Union countries -- Politics and government -- 21st century